Non-invasive Brain Stimulation in the Treatment of Post-stroke and Neurodegenerative Aphasia: Parallels, Differences, and Lessons Learned - Norise, Catherine; Hamilton, Roy H. (Frontiers in Human Neuroscience, 2017)
Numerous studies over the span of more than a decade have shown that noninvasive brain stimulation techniques, namely transcranial magnetic stimulation (TMS) and transcranial direct current stimulation (tDCS), can facilitate language recovery for patients who have suffered from aphasia due to stroke. While stroke is the most common etiology of aphasia, neurodegenerative causes of language impairment—collectively termed primary progressive aphasia (PPA)—are increasingly being recognized as important clinical phenotypes in dementia. Very limited data now suggest that noninvasive brain stimulation may have some benefit in treating PPAs. However, before applying the same approaches to patients with PPA as have previously been pursued in patients with post-stroke aphasia, it will be important for investigators to consider key similarities and differences between these aphasia etiologies that is likely to inform successful approaches to stimulation. While both post-stroke aphasia and the PPAs have clear overlaps in their clinical phenomenology, the mechanisms of injury and theorized neuroplastic changes associated with the two etiologies are notably different. Importantly, theories of plasticity in post-stroke aphasia are largely predicated on the notion that regions of the brain that had previously been uninvolved in language processing may take on new compensatory roles. PPAs, however, are characterized by slow distributed degeneration of cellular units within the language system; compensatory recruitment of brain regions to subserve language is not currently understood to be an important aspect of the condition. This review will survey differences in the mechanisms of language representation between the two etiologies of aphasia and evaluate properties that may define and limit the success of different neuromodulation approaches for these two disorders.